Rubber modified soft plastic and preparation method thereof

By using natural rubber and butyl rubber to modify polypropylene in rubber-modified soft plastics, and adding modified HPMC and BaNbO3 powder to the composite filler, the shortcomings of existing materials in antibacterial, wear resistance, aging resistance and durability are solved, and the high strength, good antibacterial properties and long life of the material are achieved.

CN119859348AActive Publication Date: 2025-04-22HUAIAN MIMIR ELECTRIC APPLIANCE CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510169786.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-04-22
Estimated Expiration
2045-02-17

AI Technical Summary

Technical Problem

Existing rubber-modified soft plastics have poor performance in antibacterial, wear resistance, aging resistance and durability, and are prone to cracks and aging, and have a short service life.

Method used

The polypropylene is modified with natural rubber and butyl rubber to form chemical bonds to enhance interface interactions, and modified HPMC and BaNbO3 powder are added to the composite filler to improve the bonding force and strength of the material by forming a good bonding layer and physical crosslinking points.

Benefits of technology

It significantly improves the strength, modulus, antibacteriality, wear resistance and aging resistance of the material, extends the service life of the material, and enhances the overall mechanical properties and flame retardant properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859348A_ABST
    Figure CN119859348A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of plastic processing, and particularly relates to rubber modified soft plastic and a preparation method thereof. The natural rubber and the butyl rubber are adopted to modify polypropylene, chemical bonds are formed between the natural rubber and the butyl rubber and the polypropylene, so that when the originally brittle polypropylene is impacted by external force, energy can be absorbed through deformation of a rubber phase, and cracking and damage are reduced; polypropylene can provide support for the rubber and limit excessive deformation of the rubber; the composite filler uses SMA modified HPMC, so that when the modified HPMC molecules are adsorbed to the surface of BaNbO3, a stable coating layer structure is formed, agglomeration among BaNbO3 particles is prevented, the modified HPMC and BaNbO3 can form chemical bonds, interface bonding between BaNbO3 and a matrix is firmer, stress can be effectively transmitted, and the stress can be effectively transmitted to the BaNbO3 from the matrix.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of plastic processing, and in particular relates to a rubber-modified soft plastic and a preparation method thereof. Background Art

[0002] Plastics have high rigidity and hardness, and good processing performance. Blending rubber with plastics to improve performance can not only improve the processing performance of plastics, but also improve the strength of rubber, making the blended material have better performance. Soft plastics generally refer to thermoplastics, polymer materials with flexibility and plasticity, which are processed by injection molding and can be processed and reused after molding. This type of plastic has the advantages of low price, soft material, and easy construction, and is widely used in various fields.

[0003] After being deformed, soft plastics are difficult to restore to their original shape and have low elasticity. Products made of rubber alone lack brittleness. The two cannot reach a balance. With the rapid development of science and technology, it is becoming more and more common to use rubber to modify soft plastics. However, the composite materials made often solve the problems of strength and toughness of the materials, but their antibacterial, wear resistance and aging resistance are still poor. They are prone to cracking and aging, with poor durability and a short service life. Therefore, how to develop a rubber-modified soft plastic with high strength, strong wear resistance, strong antibacterial, strong aging resistance and long durability is a technical problem that needs to be solved urgently. Summary of the invention

[0004] In view of the deficiencies of the prior art, the present invention provides a rubber-modified soft plastic and a preparation method thereof. The invention adopts natural rubber and butyl rubber to modify polypropylene, so that chemical bonds are formed between the natural rubber and butyl rubber and the polypropylene, and the interface interaction is enhanced, so that the bonding force is enhanced. The modified HPMC in the composite filler can form a good bonding layer at the interface of the polypropylene and the rubber, so as to enhance the bonding force between the two. BaNbO3 can improve the hardness and thermal stability of the material, and is dispersed in the polypropylene and rubber matrix, and can be used as a physical crosslinking point to restrict the movement of the molecular chain, thereby improving the strength and modulus of the material, and also improving the dielectric properties of the material. BaNbO3 powder plays a role in reinforcing the skeleton in the composite filler, thereby improving the overall strength and hardness of the material. After HPMC is combined with BaNbO3 powder, the brittleness of BaNbO3 is improved, so that the composite filler has better toughness while maintaining a certain strength, and the ability of the material to resist external force damage is improved. At the same time, HPMC interacts with groups such as hydroxyl groups in HPMC, so that a more solid interface bonding is formed between BaNbO3 and HPMC. The strengthened interface bonding can more effectively transmit stress, so that when the composite filler is subjected to external force, each component can act synergistically, thereby further enhancing the mechanical properties of the material.

[0005] In order to achieve the above technical objectives, the technical solutions adopted by the present invention are as follows: The present invention provides a rubber-modified soft plastic, which is prepared from the following raw materials in parts by weight: 60-90 parts of polypropylene, 10-40 parts of natural rubber, 5-20 parts of butyl rubber, 10-30 parts of composite filler, 1-10 parts of cross-linking agent, 3-15 parts of compatibilizer, 25-40 parts of plasticizer, 4-15 parts of ultraviolet light absorber, and 20-50 parts of flame retardant; Preferably, the cross-linking agent is hydrogen-containing silicone oil or JT-509 dealcoholization type cross-linking agent.

[0006] Preferably, the compatibilizer is one or more of KH-550 (γ-aminopropyltriethoxysilane), TEOS (tetraethyl orthosilicate), and EVA (ethylene-vinyl acetate copolymer).

[0007] Preferably, the plasticizer is epoxidized soybean oil or phenolic resin.

[0008] Preferably, the ultraviolet light absorber is benzotriazole.

[0009] Preferably, the flame retardant is zinc borate.

[0010] The raw materials for preparing the composite filler are: HPMC (hydroxypropyl cellulose), BaCl2·5H2O, Nb2O5, curcumin and SMA (styrene-maleic anhydride copolymer); the mass ratio of HPMC, BaCl2·5H2O, Nb2O5 and curcumin is 20-30:220:100:1; The preparation method of the composite filler specifically comprises the following steps: (1) Add HPMC to deionized water, stir in a water bath at 50-60°C until HPMC is completely dissolved to form a uniform HPMC solution, control the concentration of the HPMC solution to be 2-5 wt%, add SMA to the HPMC solution, the mass ratio of SMA to HPMC solution is 1-5:100, stir for 2 h to mix, obtain a mixed solution, transfer the mixed solution to a reactor, react at 120°C for 6 h to achieve the modification of HPMC, wash, and dry to obtain modified HPMC; (2) Weighing a composite alkali, mixing the composite alkali with BaCl2·5H2O and Nb2O5, wherein the mass ratio of the composite alkali to BaCl2·5H2O is 15:1, and then placing the mixture in an autoclave, reacting the mixture at 200°C for 24 h to obtain a product, neutralizing the product with dilute hydrochloric acid (pH=1), and then washing the product with deionized water and ethanol alternately, and drying the mixture in an oven to obtain BaNbO3 powder; (3) Adding modified HPMC to deionized water to control the concentration to 3-8 wt% to obtain a modified HPMC solution, adding BaNbO3 powder to the modified HPMC solution, stirring and mixing to ensure uniform dispersion, and forming a mixture A; (4) adding curcumin to the mixture A obtained in step (3), stirring and mixing to ensure uniform dispersion, thereby forming a mixture B; (5) Adding photoinitiator 1173 (2-hydroxy-2-methyl-1-phenyl-1-propanone) to the mixture B obtained in step (4), the mass ratio of the mixture B to the photoinitiator 1173 being 1:0.01-0.03, reacting under ultraviolet light of 365 nm for 1 h to carry out photopolymerization reaction to obtain HPMC / BaNbO3 precursor, curing the HPMC / BaNbO3 precursor, and then immersing it in deionized water for 24 h to remove unreacted residues, and then drying it in an oven at 40-50 °C to obtain a composite filler.

[0011] Furthermore, the composite alkali is prepared by mixing sodium hydroxide and potassium hydroxide in an equal molar ratio of 1:1.

[0012] The present invention also provides a method for preparing a rubber-modified soft plastic, which specifically comprises the following steps: S1, weighing polypropylene, natural rubber, butyl rubber and a compatibilizer in parts by weight, putting them into an internal mixer and mixing them to obtain a blend; S2, adding the crosslinking agent by weight to the blend obtained in step S1, mixing, adding the composite filler, and performing secondary mixing to mix the components evenly to obtain a mixed masterbatch; S3, adding the mixed masterbatch obtained in step S2 to a double-roll mill for refining, and then adding a plasticizer, an ultraviolet light absorber and a flame retardant to obtain a rubber compound; S4, using a twin-screw extruder to extrude the rubber mixture obtained in step S3, cooling it at room temperature, and drying it to obtain a rubber-modified soft plastic.

[0013] Furthermore, the initial temperature of the internal mixer in step S1 is 60° C., the rotor speed is 60-100 rpm, and the mixing time is 5-10 min.

[0014] Furthermore, the mixing time in step S2 is 2-10 min, and the secondary mixing time is 5-20 min.

[0015] Furthermore, in step S3, the temperature of the open refining is set to 90-120° C. and the time is set to 10-30 min.

[0016] Furthermore, the twin-screw extruder described in step S4 has a temperature set to 50-90° C. and a rotation speed set to 100-200 rpm.

[0017] Furthermore, the model of the internal mixer is RM-200C, purchased from Harbin Harp Electric Technology Co., Ltd.; the model of the twin-roll mill is 160, purchased from Guangdong Zhanjiang Rubber and Plastic Machinery Factory; the model of the twin-screw extruder is SHJ-20, purchased from Nanjing Jieente Electromechanical Co., Ltd.

[0018] Compared with the prior art, the present invention has the following beneficial effects: The invention adopts natural rubber and butyl rubber to modify polypropylene. The addition of natural rubber and butyl rubber forms chemical bonds with polypropylene, enhances the interface interaction, and enables the originally brittle polypropylene to absorb energy through the deformation of the rubber phase when subjected to external force impact, thereby reducing the possibility of cracking and damage; and the polypropylene can provide certain support for the rubber, limit the excessive deformation of the rubber, improve the overall dimensional stability and bearing capacity of the material, and make the material have both rigidity and flexibility. HPMC in the composite filler can form a good bonding layer at the interface of polypropylene and rubber, and enhance the bonding force between the two; BaNbO3 is dispersed in the polypropylene and rubber matrix, and as a physical crosslinking point, limits the movement of the molecular chain, improves the strength and modulus of the material, and also improves the dielectric properties of the material. The composite filler uses HPMC modified with SMA. SMA promotes the cross-linking structure of the originally linear molecular chain of HPMC, increases the steric hindrance effect of the molecular chain, and enables the modified HPMC molecules to better interweave and entangle with each other when adsorbed on the surface of BaNbO3, forming a stable coating layer structure, preventing the agglomeration of BaNbO3 particles, and making BaNbO3 highly uniformly dispersed in the rubber-modified soft plastic as a whole, avoiding local performance differences, and improving the stability and consistency of the overall performance of the material. The modified HPMC can form a chemical bond with BaNbO3, and its strength is much higher than that of hydrogen bonds and van der Waals forces, so that the interface between BaNbO3 and the rubber-modified soft plastic as a whole is more firmly bonded, and can effectively transfer stress, so that the stress can be transferred from the rubber-modified soft plastic as a whole to BaNbO3. When the material is subjected to external force, the interfacial bonding force strengthened by HPMC accurately and efficiently transfers stress from the rubber-modified soft plastic as a whole to BaNbO3, promoting synergistic deformation. This process can effectively interfere with and block the crack propagation path, making the energy distribution inside the material more uniform and maintaining the toughness of the material; BaNbO3 is evenly dispersed in the rubber-modified soft plastic as a whole, and the modified HPMC builds a good interface bridge, so that the charge can be smoothly conducted and stored inside the material, achieving excellent electrical properties. When subjected to force, the stress can be evenly distributed in the entire material system, avoiding damage caused by local stress concentration and ensuring the mechanical properties of the material. When the curcumin added to the composite filler undergoes a photopolymerization reaction, the curcumin interacts with the system formed by HPMC and BaNbO3, which, on the one hand, helps the photopolymerization reaction and makes the structure of the composite filler more stable; on the other hand, in the subsequent use process, it can absorb ultraviolet rays, reduce the damage of ultraviolet rays to the composite filler and the applied materials, and improve the light aging resistance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 A schematic cross-sectional view of a microscopic model of the rubber-modified soft plastic prepared in the present invention; Figure 2A line graph showing the limiting oxygen index of the rubber-modified soft plastic prepared by the present invention; Figure 3 This is a bar chart showing the aging resistance of the rubber-modified soft plastic prepared in the present invention. DETAILED DESCRIPTION

[0020] In order to make the technical solution of the present invention better understood by the technical personnel in the field, and to make the above-mentioned features, purposes and advantages of the present invention more clearly understood, the present invention is further described below in conjunction with the embodiments. The embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0021] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0022] In the following examples, unless otherwise specified, conventional methods are used; the materials used in the following examples, unless otherwise specified, are all new materials purchased from the market, wherein polypropylene, CAS No.: 9003-07-0, molecular weight: 80000-90000, melt index: 0.3 g / 10 min, was purchased from Sinopec; natural rubber, CAS No.: 9006-04-6, was purchased from Shanghai McLean Reagent Co., Ltd.; butyl rubber, model: 1751, was purchased from Beijing Yanshan Petrochemical Co., Ltd.; HPMC, 2% viscosity: 6 mPa.s, methoxy Base: 28-30%; Hydroxypropyl: 7.0-12%, purchased from Aladdin Reagent Co., Ltd.; Curcumin, product number: C805204, reagent grade, purchased from Shanghai McLean Reagent Co., Ltd.; SMA, maleic anhydride (MAH) content is 12.5%, purchased from Shanghai Petrochemical Research Institute; Benzotriazole, CAS number: 95-14-7, product number: H801875, 99%, purchased from Shanghai McLean Reagent Co., Ltd.; Phenolic resin, CAS number: 9003-35-4, product number: P832682, BR, purchased from Shanghai McLean Reagent Co., Ltd.

[0023] Example 1: This example provides a rubber-modified soft plastic, which is prepared from the following raw materials in parts by weight: 60 parts of polypropylene, 40 parts of natural rubber, 5 parts of butyl rubber, 10 parts of composite filler, 1 part of hydrogenated silicone oil, 3 parts of KH-550, 25 parts of epoxy soybean oil, 4 parts of benzotriazole, and 20 parts of zinc borate; The raw materials for preparing the composite filler are: HPMC, BaCl2·5H2O, Nb2O5, curcumin and SMA; the mass ratio of HPMC, BaCl2·5H2O, Nb2O5 and curcumin is 20:220:100:1; The preparation method of the composite filler specifically comprises the following steps: (1) 30 parts of HPMC were added to deionized water, and stirred at 500 rpm in a 50 ℃ water bath until HPMC was completely dissolved to form a uniform HPMC solution. The concentration of the HPMC solution was controlled to be 2 wt%. SMA was added to the HPMC solution, and the mass ratio of SMA to HPMC solution was 1:100. The mixture was stirred at 500 rpm for 2 h to obtain a mixed solution. The mixed solution was transferred into a polytetrafluoroethylene-lined autoclave and reacted at 120 ℃ for 6 h to achieve the modification of HPMC. The mixture was washed alternately with deionized water and anhydrous ethanol for 3 times, and dried in an oven at 60 ℃ for 12 h to obtain modified HPMC. (2) Sodium hydroxide and potassium hydroxide are mixed in an equimolar ratio of 1:1 to form a composite hydroxide. Then, the composite hydroxide is mixed with BaCl2·5H2O and Nb2O5. The mass ratio of the composite hydroxide to BaCl2·5H2O is 15:1. Then, the composite hydroxide is placed in an autoclave and reacted at 200°C for 24 h to obtain a product. The product is neutralized with dilute hydrochloric acid (pH=1). Then, the product is rinsed with deionized water and ethanol alternately for 3 times and dried in an oven at 70°C to obtain BaNbO3 powder. (3) Adding modified HPMC to deionized water to control the concentration to 3 wt% to obtain a modified HPMC solution, adding BaNbO3 powder to the modified HPMC solution, placing it in an ultrasonic cleaning machine, and mixing it at 240 W for 1 h to ensure uniform dispersion to form a mixture A; (4) adding curcumin to the mixture A obtained in step (3), stirring at 800 rpm to ensure uniform dispersion, to form a mixture B; (5) Adding photoinitiator 1173 to the mixture B obtained in step (4) in a mass ratio of mixture B to photoinitiator 1173 of 1:0.01, reacting under 365 nm ultraviolet light for 1 h to perform photopolymerization reaction to obtain HPMC / BaNbO3 precursor, curing the HPMC / BaNbO3 precursor at room temperature for 12 h, and then immersing it in deionized water for 24 h to remove unreacted residues, and then drying it in an oven at 40°C to obtain a composite filler.

[0024] This embodiment also provides a method for preparing a rubber-modified soft plastic, which specifically includes the following steps: S1, weigh 60 parts of polypropylene, 40 parts of natural rubber, 5 parts of butyl rubber and 3 parts of KH-550, put them into an internal mixer and mix them for 5 min. The initial temperature of the internal mixer is 60 °C and the rotor speed is 60 rpm to obtain a blend; S2, weighing 1 part of hydrogen-containing silicone oil, adding it to the blend obtained in step S1, continuing to mix in an internal mixer for 2 minutes, adding 10 parts of composite filler, and performing secondary mixing for 20 minutes to mix the components evenly to obtain a mixed masterbatch; S3, putting the mixed masterbatch obtained in step S2 into a two-roll mill for refining for 10 min, adding 25 parts of epoxy soybean oil, 4 parts of benzotriazole and 20 parts of zinc borate, mixing evenly, setting the temperature to 90°C, and obtaining a mixed rubber; S4, using a twin-screw extruder to extrude the rubber mixture obtained in step S3, setting the temperature of the twin-screw extruder to 50° C. and the rotation speed to 100 rpm, cooling at room temperature, and drying to obtain a rubber-modified soft plastic.

[0025] Example 2: This example provides a rubber-modified soft plastic, which is prepared from the following raw materials in parts by weight: 70 parts of polypropylene, 30 parts of natural rubber, 10 parts of butyl rubber, 18 parts of composite filler, 2 parts of JT-509 dealcoholization crosslinking agent, 7 parts of compatibilizer, 30 parts of phenolic resin, 8 parts of benzotriazole, and 30 parts of zinc borate; The compatibilizers are KH-550 and TEOS, and the molar ratio of the two is 1:1.

[0026] The raw materials for preparing the composite filler are: HPMC, BaCl2·5H2O, Nb2O5, curcumin and SMA; the mass ratio of HPMC, BaCl2·5H2O, Nb2O5 and curcumin is 24:220:100:1; The preparation method of the composite filler specifically comprises the following steps: (1) 30 parts of HPMC were added to deionized water, and stirred at 500 rpm in a water bath at 55 °C until HPMC was completely dissolved to form a uniform HPMC solution. The concentration of the HPMC solution was controlled to be 3 wt%. SMA was added to the HPMC solution at a mass ratio of SMA to HPMC solution of 2:100. The mixture was stirred at 500 rpm for 2 h to obtain a mixed solution. The mixed solution was transferred into a polytetrafluoroethylene-lined autoclave and reacted at 120 °C for 6 h to achieve the modification of HPMC. The mixture was washed alternately with deionized water and anhydrous ethanol for 3 times and dried in an oven at 60 °C for 12 h to obtain modified HPMC. (2) Sodium hydroxide and potassium hydroxide are mixed in an equimolar ratio of 1:1 to form a composite hydroxide. Then, the composite hydroxide is mixed with BaCl2·5H2O and Nb2O5. The mass ratio of the composite hydroxide to BaCl2·5H2O is 15:1. Then, the composite hydroxide is placed in an autoclave and reacted at 200°C for 24 h to obtain a product. The product is neutralized with dilute hydrochloric acid (pH=1). Then, the product is rinsed with deionized water and ethanol alternately for 3 times and dried in an oven at 70°C to obtain BaNbO3 powder. (3) Adding modified HPMC to deionized water to control the concentration to 5 wt% to obtain a modified HPMC solution, adding BaNbO3 powder to the modified HPMC solution, placing the solution in an ultrasonic cleaning machine, and mixing at 240 W for 2 h to ensure uniform dispersion to form a mixture A; (4) adding curcumin to the mixture A obtained in step (3), stirring at 800 rpm to ensure uniform dispersion, to form a mixture B; (5) Adding photoinitiator 1173 to the mixture B obtained in step (4) in a mass ratio of mixture B to photoinitiator 1173 of 1:0.015, reacting under 365 nm ultraviolet light for 1 h to perform photopolymerization reaction to obtain HPMC / BaNbO3 precursor, curing the HPMC / BaNbO3 precursor at room temperature for 12 h, and then immersing it in deionized water for 24 h to remove unreacted residues, and then drying it in an oven at 50°C to obtain a composite filler.

[0027] This embodiment also provides a method for preparing a rubber-modified soft plastic, which specifically includes the following steps: S1, weigh 70 parts of polypropylene, 30 parts of natural rubber, 10 parts of butyl rubber and 7 parts of compatibilizer, put them into an internal mixer and mix them for 7 min. The initial temperature of the internal mixer is 60 °C and the rotor speed is 75 rpm to obtain a blend; S2, weighing 2 parts of JT-509 dealcoholization crosslinking agent, adding them to the blend obtained in step S1, continuing to mix in an internal mixer for 5 min, adding 18 parts of composite filler, and mixing again for 10 min to mix all the components evenly to obtain a mixed masterbatch; S3, putting the mixed masterbatch obtained in step S2 into a two-roll mill for milling for 15 min, then adding 30 parts of phenolic resin, 8 parts of benzotriazole and 30 parts of zinc borate, mixing evenly, setting the temperature to 100° C., and obtaining a mixed rubber; S4, using a twin-screw extruder to extrude the rubber mixture obtained in step S3, setting the temperature of the twin-screw extruder to 60° C. and the rotation speed to 130 rpm, cooling at room temperature, and drying to obtain a rubber-modified soft plastic.

[0028] Example 3: This example provides a rubber-modified soft plastic, which is prepared from the following raw materials in parts by weight: 80 parts of polypropylene, 20 parts of natural rubber, 15 parts of butyl rubber, 20 parts of composite filler, 6 parts of JT-509 dealcoholization crosslinking agent, 10 parts of TEOS, 35 parts of phenolic resin, 10 parts of benzotriazole, and 40 parts of zinc borate; The raw materials for preparing the composite filler are: HPMC, BaCl2·5H2O, Nb2O5, curcumin and SMA; the mass ratio of HPMC, BaCl2·5H2O, Nb2O5 and curcumin is 25:220:100:1; The preparation method of the composite filler specifically comprises the following steps: (1) 40 parts of HPMC were added to deionized water, and stirred at 500 rpm in a water bath at 60 °C until HPMC was completely dissolved to form a uniform HPMC solution. The concentration of the HPMC solution was controlled to be 4 wt%. SMA was added to the HPMC solution, and the mass ratio of SMA to HPMC solution was 3:100. The mixture was stirred at 500 rpm for 2 h to obtain a mixed solution. The mixed solution was transferred into a polytetrafluoroethylene-lined autoclave and reacted at 120 °C for 6 h to achieve the modification of HPMC. The mixture was washed alternately with deionized water and anhydrous ethanol for 3 times, and dried in an oven at 60 °C for 12 h to obtain modified HPMC. (2) Sodium hydroxide and potassium hydroxide are mixed in an equimolar ratio of 1:1 to form a composite hydroxide. Then, the composite hydroxide is mixed with BaCl2·5H2O and Nb2O5. The mass ratio of the composite hydroxide to BaCl2·5H2O is 15:1. Then, the composite hydroxide is placed in an autoclave and reacted at 200°C for 24 h to obtain a product. The product is neutralized with dilute hydrochloric acid (pH=1). Then, the product is rinsed with deionized water and ethanol alternately for 3 times and dried in an oven at 70°C to obtain BaNbO3 powder. (3) Adding modified HPMC to deionized water to control the concentration to 6 wt% to obtain a modified HPMC solution, adding BaNbO3 powder to the modified HPMC solution, placing it in an ultrasonic cleaning machine, and mixing it at 240 W for 2.5 h to ensure uniform dispersion to form a mixture A; (4) adding curcumin to the mixture A obtained in step (3), stirring at 800 rpm to ensure uniform dispersion, to form a mixture B; (5) Adding photoinitiator 1173 to the mixture B obtained in step (4) in a mass ratio of mixture B to photoinitiator 1173 of 1:0.02, reacting under 365 nm ultraviolet light for 1 h to perform photopolymerization reaction to obtain HPMC / BaNbO3 precursor, curing the HPMC / BaNbO3 precursor at room temperature for 12 h, and then immersing it in deionized water for 24 h to remove unreacted residues, and then drying it in an oven at 50°C to obtain a composite filler.

[0029] This embodiment also provides a method for preparing a rubber-modified soft plastic, which specifically includes the following steps: S1, weigh 80 parts of polypropylene, 20 parts of natural rubber, 15 parts of butyl rubber and 10 parts of TEOS, put them into an internal mixer and mix them for 9 minutes. The initial temperature of the internal mixer is 60 °C and the rotor speed is 90 rpm to obtain a blend; S2, weigh 6 parts of JT-509 dealcoholization crosslinking agent, add it to the blend obtained in step S1, continue to mix in the internal mixer for 7 minutes, add 20 parts of composite filler, and mix again for 15 minutes to mix all the components evenly to obtain a mixed masterbatch; S3, putting the mixed masterbatch obtained in step S2 into a double-roll mill for refining for 20 min, then adding 35 parts of phenolic resin, 10 parts of benzotriazole and 40 parts of zinc borate, mixing evenly, setting the temperature to 110° C., and obtaining a rubber mixture; S4, using a twin-screw extruder to extrude the rubber mixture obtained in step S3, setting the temperature of the twin-screw extruder to 70° C. and the rotation speed to 160 rpm, cooling at room temperature, and drying to obtain a rubber-modified soft plastic.

[0030] Example 4: This example provides a rubber-modified soft plastic, which is prepared from the following raw materials in parts by weight: 90 parts of polypropylene, 10 parts of natural rubber, 20 parts of butyl rubber, 30 parts of composite filler, 10 parts of JT-509 dealcoholization crosslinking agent, 15 parts of EVA, 40 parts of phenolic resin, 15 parts of benzotriazole, and 50 parts of zinc borate; The raw materials for preparing the composite filler are: HPMC, BaCl2·5H2O, Nb2O5, curcumin and SMA; the mass ratio of HPMC, BaCl2·5H2O, Nb2O5 and curcumin is 30:220:100:1; The preparation method of the composite filler specifically comprises the following steps: (1) Add 50 parts of HPMC to deionized water, stir at 500 rpm in a water bath at 60 °C until HPMC is completely dissolved to form a uniform HPMC solution, control the concentration of the HPMC solution at 5 wt%, add SMA to the HPMC solution, the mass ratio of SMA to HPMC solution is 5:100, stir at 500 rpm for 2 h to obtain a mixed solution, transfer the mixed solution into a polytetrafluoroethylene-lined autoclave, react at 120 °C for 6 h to achieve the modification of HPMC, wash with deionized water and anhydrous ethanol alternately for 3 times, and dry in an oven at 60 °C for 12 h to obtain modified HPMC; (2) Sodium hydroxide and potassium hydroxide are mixed in an equimolar ratio of 1:1 to form a composite hydroxide. Then, the composite hydroxide is mixed with BaCl2·5H2O and Nb2O5. The mass ratio of the composite hydroxide to BaCl2·5H2O is 15:1. Then, the composite hydroxide is placed in an autoclave and reacted at 200°C for 24 h to obtain a product. The product is neutralized with dilute hydrochloric acid (pH=1). Then, the product is rinsed with deionized water and ethanol alternately for 3 times and dried in an oven at 70°C to obtain BaNbO3 powder. (3) Adding modified HPMC to deionized water to control the concentration to 8 wt% to obtain a modified HPMC solution, adding BaNbO3 powder to the modified HPMC solution, placing the solution in an ultrasonic cleaning machine, and mixing at 240 W for 3 h to ensure uniform dispersion to form a mixture A; (4) adding curcumin to the mixture A obtained in step (3), stirring at 800 rpm to ensure uniform dispersion, to form a mixture B; (5) Adding photoinitiator 1173 to the mixture B obtained in step (4) in a mass ratio of mixture B to photoinitiator 1173 of 1:0.03, reacting under 365 nm ultraviolet light for 1 h to perform photopolymerization reaction to obtain HPMC / BaNbO3 precursor, curing the HPMC / BaNbO3 precursor at room temperature for 12 h, and then immersing it in deionized water for 24 h to remove unreacted residues, and then drying it in an oven at 50°C to obtain a composite filler.

[0031] This embodiment also provides a method for preparing a rubber-modified soft plastic, which specifically includes the following steps: S1, weigh 90 parts of polypropylene, 10 parts of natural rubber, 20 parts of butyl rubber and 15 parts of EVA, put them into an internal mixer and mix them for 10 min. The initial temperature of the internal mixer is 60 °C and the rotor speed is 100 rpm to obtain a blend; S2, weighing 10 parts of JT-509 dealcoholization crosslinking agent, adding it to the blend obtained in step S1, continuing to mix in the internal mixer for 10 min, adding 30 parts of composite filler, and mixing again for 20 min to mix the components evenly to obtain a mixed masterbatch; S3, putting the mixed masterbatch obtained in step S2 into a double-roll mill for 30 min, then adding 40 parts of phenolic resin, 15 parts of benzotriazole and 50 parts of zinc borate, mixing evenly, setting the temperature to 120° C., and obtaining a mixed rubber; S4, using a twin-screw extruder to extrude the rubber mixture obtained in step S3, setting the temperature of the twin-screw extruder to 90° C. and the rotation speed to 200 rpm, cooling at room temperature, and drying to obtain a rubber-modified soft plastic.

[0032] The difference between Comparative Example 1 and Example 1 is that the addition of natural rubber is eliminated, and the rest is the same as Example 1.

[0033] The difference between Comparative Example 2 and Example 1 is that the addition of butyl rubber is eliminated, and the rest is the same as Example 1.

[0034] The difference between Comparative Example 3 and Example 1 is that the addition of the composite filler is eliminated, and the rest is the same as Example 1.

[0035] The difference between Comparative Example 4 and Example 1 is that the preparation method of the composite filler is as follows: HPMC is added to deionized water, the concentration of the HPMC solution is controlled to be 2-5 wt%, and the mixture is stirred at a speed of 500 rpm in a water bath of 50-60 ° C until the HPMC is completely dissolved to form a uniform HPMC solution; BaCl2·5H2O and Nb2O5 are mixed to form a mixed solution, and then the mixed solution is placed in an autoclave, and reacted at 200 ° C for 24 h to obtain a product, and the product is neutralized with dilute hydrochloric acid (pH=1), and then the product is alternately rinsed with deionized water and ethanol for 3 times, and placed in an oven at 70 ° C to dry to obtain BaNbO3 powder; BaNbO3 powder is added to the HPMC solution, placed in an ultrasonic cleaning machine, and mixed at 240 W for 1-3 h to ensure uniform dispersion to form a mixture A; curcumin is added to the mixture A, and stirred at a speed of 800 rpm to ensure uniform dispersion to form a mixture B; the mixture B is placed in a 90 The mixture was reacted in a water bath at ℃ for 4 h, and then taken out and dried to obtain a composite filler.

[0036] Experimental example Tensile performance test: According to GB / T528-2009, the test was carried out using a TCS-2000 computer system tensile testing machine of China High Speed ​​Rail Testing Instrument Co., Ltd. at a tensile speed of 5 mm / min. The rubber-modified soft plastics prepared in Examples 1-4 and Comparative Examples 1-4 were used to prepare test specimens by cutting the initial specimens in the middle and then naturally splicing them. The tensile test was carried out after repairing at 30°C for 20 min. The tensile test was carried out three times, and the average tensile strength was calculated. The calculation results are recorded in Table 1.

[0037] Shore A hardness test: GB / T2411-2008 was used to perform the hardness test. Samples were prepared using the rubber-modified soft plastics prepared in Examples 1-4 and Comparative Examples 1-4, respectively. The samples were placed on a hard, solid horizontal plane. The hardness tester was held in a vertical position with the tip of the pressure needle 10 mm away from any edge of the sample. The pressure seat was immediately added to the sample without impact, so that the pressure seat was parallel to the sample and sufficient pressure was applied. The pressure seat was in close contact with the sample. After 15 seconds, the indication of the indicator was read. Five hardness values ​​were measured on the same sample at an interval of 6 mm, and the average value was calculated. The calculated hardness average value is recorded in Table 1.

[0038] Aging resistance test: The rubber-modified soft plastics prepared in Examples 1-4 and Comparative Examples 1-4 were used to make 2 mm dumbbell-shaped specimens on a punching machine. After aging in an oven at 70°C for 72 h, the performance was measured and the average value was taken as P1. The other groups were directly tested and the average value P0 was taken. The formula for heat aging performance retention rate is: P=P1 / P0×100%, where P0 is the performance of the specimen before heat aging, P1 is the performance of the specimen after heat aging, and P is the heat aging performance retention rate of the specimen (%). The calculated heat aging performance retention rate results are recorded in Table 1.

[0039] Antibacterial performance test: The antibacterial test was carried out by the film sticking method. The rubber-modified soft plastics prepared in Examples 1-4 and Comparative Examples 1-4 were used to prepare smooth test specimens. The size of the test specimens was 50 mm×50 mm×5 mm (length×width×thickness). The test strain was Escherichia coli (SHBCCD80636) ordered from Shanghai Collection Biotechnology Center. The Escherichia coli was resuscitated and cultured for 24 h. An appropriate amount of Escherichia coli was selected and placed in sterile physiological saline for mixing and dilution to form a bacterial suspension. All the test specimens were disinfected, cleaned, dried and set aside. A single test specimen was placed in a sterile culture dish. The bacterial suspension was absorbed by a dropper. 0.05 ml of the bacterial suspension was dripped onto the surface of the test specimen. The specimen was placed in a culture dish to receive the bacterial suspension. The culture dish cover was then covered. The sample was placed in a constant temperature incubator and cultured for 24 hours. h; Use an equal amount of eluent to elute the colonies in each test specimen and the control specimen, count the number of live bacteria in the eluent and calculate the antibacterial rate in accordance with the Technical Specifications for Disinfection. The calculation results of each test specimen are shown in Table 1.

[0040] Impact strength test: The impact strength test was conducted according to GB / T 1843-2008. The rubber-modified soft plastics prepared in Examples 1-4 and Comparative Examples 1-4 were used to make test specimens of 80 mm×10 mm×4 mm, respectively. The impact strength was tested by a cantilever beam test. The pendulum was lifted and locked. When the notched specimen was tested, the notch was on the side where the pendulum impacted the toughness. The pendulum was released and the impact energy absorbed by the specimen was recorded. For the unnotched specimen, the impact strength was calculated according to the following formula: a iN =(E C / h×b N ) × 10 3 , where E c is the corrected sample fracture absorption energy in joules (J), h is the sample thickness in millimeters (mm), b N is the remaining width of the sample, in millimeters (mm). The average value of the test results is recorded in Table 1.

[0041] Table 1

[0042] The results in Table 1 show that the tensile strength, Shore hardness, aging resistance, antibacterial property and impact strength of Examples 1-4 are significantly higher than those of Comparative Examples 1-4, indicating that the performance of the rubber-modified soft plastic prepared by the present invention is significantly improved, and the interaction between the materials makes the rubber-modified soft plastic have excellent performance; Figure 1 This is a schematic diagram of the rubber-modified soft plastic prepared by the present invention. From the enlarged view, it can be seen that the modified HPMC is cross-linked with the BaNbO3 molecular chain, tightly wrapping the BaNbO3, making the dispersion more uniform and the combination more firm; Figure 2The limiting oxygen index of the rubber-modified soft plastic prepared by the present invention is shown, and the limiting oxygen index is much higher than the self-extinguishing requirement of 27%, indicating that the rubber-modified soft plastic prepared by the present invention has good flame retardant properties; Figure 3 It is shown that the aging resistance of comparative examples 1-4 is significantly lower than that of embodiments 1-4, and when butyl rubber is not added, the aging resistance is poor, indicating that the interaction between butyl rubber and other materials significantly improves the aging resistance of soft plastics.

[0043] In summary, by introducing natural rubber and butyl rubber into the soft plastic polypropylene, the wear resistance and impact resistance of the material are significantly improved. The combination of modified HPMC and BaNbO3 powder in the composite filler improves the brittleness of BaNbO3, so that the composite filler has better toughness while maintaining high strength. At the same time, it interacts with groups such as hydroxyl groups in HPMC to form a stronger interface bond between BaNbO3 and HPMC, thereby enhancing the mechanical properties of the material and imparting it with antibacterial properties. The cross-linking agent promotes the cross-linking of each material, so that materials with different polarities can be more firmly combined with each other. The solubilizer also improves the oil resistance of the material. Through the interaction between each material, the rubber-modified soft plastic prepared by the present invention has good mechanical properties, antibacterial properties, aging resistance and flame retardancy, and can be widely used in the fields of automobiles, construction, electronics, medical treatment, sports equipment and consumer products.

[0044] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A rubber-modified soft plastic, characterized in that: The invention is prepared from the following raw materials in parts by weight: 60-90 parts of polypropylene, 10-40 parts of natural rubber, 5-20 parts of butyl rubber, 10-30 parts of composite filler, 1-10 parts of cross-linking agent, 3-15 parts of compatibilizer, 25-40 parts of plasticizer, 4-15 parts of ultraviolet light absorber and 20-50 parts of flame retardant; The raw materials for preparing the composite filler are: HPMC, BaCl2·5H2O, Nb2O5, curcumin and SMA; the mass ratio of HPMC, BaCl2·5H2O, Nb2O5 and curcumin is 20-30:220:100:1; The preparation method of the composite filler specifically comprises the following steps: (1) Adding HPMC to deionized water, stirring in a water bath to form a uniform HPMC solution, adding SMA to the HPMC solution, stirring and mixing to obtain a mixed solution, and then subjecting the mixed solution to a solvothermal reaction, washing, and drying to obtain a modified HPMC; (2) weighing a composite alkali, mixing the composite alkali with BaCl2·5H2O and Nb2O5, and then performing a solvothermal reaction to obtain a product, neutralizing the product, and then washing and drying the product to obtain BaNbO3 powder; (3) adding the modified HPMC into deionized water to obtain a modified HPMC solution, adding the BaNbO3 powder into the modified HPMC solution, and mixing them evenly to form a mixture A; (4) adding curcumin to the mixture A obtained in step (3), stirring and mixing to form a mixture B; (5) Adding photoinitiator 1173 to the mixture B obtained in step (4) to carry out photopolymerization reaction to obtain HPMC / BaNbO3 precursor, curing the HPMC / BaNbO3 precursor, and then immersing it in deionized water, and then drying it to obtain a composite filler.

2. The rubber-modified soft plastic according to claim 1, characterized in that: The cross-linking agent is hydrogen-containing silicone oil or JT-509 dealcoholization type cross-linking agent.

3. The rubber-modified soft plastic according to claim 1, characterized in that: The compatibilizer is one or more of KH-550, TEOS and EVA.

4. The rubber-modified soft plastic according to claim 1, characterized in that: The plasticizer is epoxy soybean oil or phenolic resin, the ultraviolet light absorber is benzotriazole, and the flame retardant is zinc borate.

5. The rubber-modified soft plastic according to claim 1, characterized in that: In step (1), the concentration of the HPMC solution is 2-5 wt%, and the mass ratio of the SMA to the HPMC solution is 1-5:

100.

6. The rubber-modified soft plastic according to claim 1, characterized in that: In step (2), the mass ratio of the composite alkali to BaCl2·5H2O is 15:1, the temperature of the solvent thermal reaction is set to 200°C, and the time is set to 24 h.

7. The rubber-modified soft plastic according to claim 1, characterized in that: In step (3), the concentration of the modified HPMC solution is 3-8 wt %. In step (5), the mass ratio of the mixture B to the photoinitiator 1173 is 1:0.01-0.

03. The photopolymerization reaction is carried out under ultraviolet light of 365 nm for 1 h.

8. A method for preparing the rubber-modified soft plastic according to any one of claims 1 to 7, characterized in that: The specific steps include: S1, weighing polypropylene, natural rubber, butyl rubber and a compatibilizer in parts by weight, and mixing them to obtain a blend; S2, adding the crosslinking agent by weight to the blend obtained in step S1, kneading, and then adding the composite filler, kneading for a second time, mixing, and obtaining a mixed masterbatch; S3, refining the mixed masterbatch obtained in step S2, adding a plasticizer, an ultraviolet light absorber and a flame retardant according to weight, and mixing them to obtain a mixed rubber; S4, extruding, cooling and drying the rubber mixture obtained in step S3 to obtain a rubber-modified soft plastic.

Citation Information

Patent Citations

  • Preparation method for graft-modified hydrophobic associated polymer

    CN108546316A

  • Rigid particle reinforced and flexibilized polypropylene material and its prepn. method

    CN1323853A

  • Thermoplastic elastomer produced from waste rubber powder / plastic and the article made therefrom

    WO2001014464A1

  • Modified hydroxypropyl methyl cellulose for enhanced ceramic tile adhesive, and preparation method therefor and use thereof

    WO2022007454A1